Legal Constitutions of Working Accidents and Work Force Losses in Turkey - İnce, Cengiz Haluk; İnce, Nurhan; Tüzün, Birgül (The Bulletin of Legal Medicine, 2000)
When workers force the diseases or injuries that are not treatable the following losses are calculated by several laws. However there are several differences between cases of officers and workers in these law and instruction. Inefficiency of figuring out disability with aging and emphasizing a standardization study for protection of the rights of the workers have been the main goals of this study. A total of 1 law and 2 interactions about disability and restricted work activity are studied both separately and comparatively. These differences and legal gaps may cause right losses and several inequalities between workers who disability calculation and other legal arrangements are made. The case of blue collar workers are evaluated by the law, declared in I960 and white collar workers are evaluated by a different law declared in 1953. These law and instructions should rearrangement and must be used for all workers as a standard.Key Words: : Work force losses, disability, law.
Keywords: work force losses; disability; law